Pola Pendidikan Kyai Abdul Malik Luqoni Pengasuh Pondok Pesantren Minhajut Thullab Sumberberas Muncar Banyuwangi - Sumari Mawardi (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
This research is formulated in two questions: 1) how the pattern of education Kyai Luqoni. 2) how the application of the pattern of education in the present. The method in this research is a descriptive method with a qualitative approach. The informants were Kyai Luqoni's family and the Bani Mannan family, as well as the alumni of the board who were still linked. Determination of informants is done by snowball technique. Data collection was done by interview, observation. Data analysis was done by Miles and Huberman analysis model: data reduction, display data, and conclusion drawing/verification. The results of data analysis show the existence of efforts to develop aspects of cognitive, affective, and psychomotor in educational activities Kyai Luqoni Development of these three aspects which become indications of a reference to be made tauladan. Implementation in the present day is also very important to be implemented in the realm of family, santri, and society